(untitled) (LACCEI, 2024)
The objective of this research was to analyze the relationship between the managerial skills of MSME managers and the competitive advantage of the companies. The study sample is composed of companies located in the provinces of Barranca, Huaura and Huaral in Peru. A quantitative approach was used by applying surveys to the managers of the selected companies. The results indicate that managerial skills are significantly related to competitive advantage, both in the customer/market dimension and in the economic-financial dimension. The results indicate that managerial skills maintain a certain relationship with competitive advantage, considering that there was a correlation of 0.59 between the variables with Spearman’s Rho coefficient. In addition, it was found with the longitudinal logistic regression that at least one predictor variable has a significant effect with the response variable, confirmed by [1][10][11][15], for the reliability Alpha of 0.83 in managerial skills with nonparametric distribution and competitive advantage of 0.71. The findings indicate that, if creative ideas are applied, it is possible to solve complex situations that always exist in the Mypes with a certainty of 52.39, also, with listening it is possible to improve dialogue and communication.